Depressive disorders before and after coronary artery bypass graft (Bangladesh Journal of Psychiatry, 2019)
Chronic diseases had numerous psychiatric consequences where depression was the prime concern. Coronary artery bypass graft (CABG) surgery strongly affected mental health of patients. Current study was aimed at assessing proportion and quantifying severity of depressive disorders among patients before and after CABG. This longitudinal study was conducted in the department of Psychiatry, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the period July 2014 to June 2015. A total of 104 patients were interviewed purposively after getting informed written consent with the semi-structured questionnaire, structured clinical interview for the DSM IV Axis I disorders clinician version (SCID I CV) and Bangla version of depression anxiety stress scale 21 (DASS 21). The results showed that proportion and severity of depressive disorders was significantly increased after CABG surgery than before surgery. Before CABG, 49% of patients were suffering from depressive disorders and after CABG, depressive disorders were found in 68.3% patients. Severity scoring before CABG revealed 6.7% were severe, 17.3% were moderate and 25% were mild. On the contrary, after CABG severity scoring revealed 15.4% were severe, 33.7% were moderate and 19.2% were mild. Severity of depressive disorders was significantly increased after CABG (p=0.002). Depressive disorders were prevalent among patients with coronary artery disease (CAD) undergoing CABG surgery. Broad based multi centered long-term longitudinal study could be carried out to draw inferences. Strong Consultation-liaison psychiatric services should be needed to provide proper treatment for depressive disorders of patients undergoing CABG.Bang J Psychiatry 2019; 33(1): 7-10